Immunoglobulin G (IgG) subclass deficiency in Thai children - Nualanong Visitsunthorn (2018)
Background: Patients with Immunoglobulin G (IgG) subclass deficiency may suffer from recurrent infections, mainly sino-pulmonary infection. Objective: To determine the epidemiology of IgG subclass deficiency in Thai children at a tertiary care hospital and to compare the differences between children who were diagnosed with IgG subclass deficiency by using low level criteria [less than 2 standard deviation (SD) of normal levels for age] and by using low percentage criteria (proportion of each IgG subclasses/total IgG). Methods: The study was a descriptive study of 55 children up to 15 years old with recurrent infections diagnosed as having IgG subclass deficiency but no acquired or other primary immune deficiencies except for IgA and/or IgM deficiency. Result: Isolated IgG3 subclass deficiency was the most common IgG subclass deficiency (56.4%). IgG3 subclass deficiency, either isolated or combined with other IgG subclass deficiency, was found in 85.5% of the cases. The common age of onset was between birth and five years of age. The most common presenting symptom was recurrent sinusitis (83.6%). Majority of the cases (89.3%) were diagnosed by low percentage criteria while 12.7% were diagnosed by low level criteria. All cases with low levels of IgG subclass antibodies also had low percentages. There were no statistically significant differences in the clinical manifestations and management methods between the children who were diagnosed by low level and low percentage. Conclusion: IgG3 subclass deficiency was the most common IgG subclass deficiency in Thai children. The most common presenting symptom was recurrent sinusitis. Although the diagnosis could be made in the patients with recurrent upper respiratory infection by using low level criteria, but the diagnosis should be considered when the low percentage criteria are met.